Short-Term Antiandrogen Flutamide Treatment Causes Structural Alterations in Somatic Cells Associated with Premature Detachment of Spermatids in the Testis of Pubertal and Adult Guinea Pigs - Maschio, L. R. [UNESP]; Cordeiro, R. S. [UNESP]; Taboga, S. R. [UNESP]; Goes, R. M. [UNESP] (Wiley-Blackwell, 2010)
ContentsIn spite of widespread application of flutamide in the endocrine therapies of young and adult patients, the side effects of this antiandrogen on spermatogenesis and germ-cell morphology remain unclear. This study evaluates the short-term androgen blockage effect induced by the administration of flutamide to the testes of pubertal (30-day old) and adult (65- and 135-day old) guinea pigs, with an emphasis on ultrastructural alterations of main cell types. The testes removed after 10 days of treatment with either a non-steroidal antiandrogen, flutamide (10 mg/kg of body weight) or a pharmacological vehicle alone were processed for histological, quantitative and ultrastructural analysis. In pubertal animals, flutamide androgenic blockage induces spermatogonial differentiation and accelerates testes maturation, causing degeneration and detachment of primary spermatocytes and round spermatids, which are subsequently found in great quantities in the epididymis caput. In post-pubertal and adult guinea pigs, in addition to causing germ-cell degeneration, especially in primary spermatocytes, and leading to the premature detachment of spherical spermatids, the antiandrogen treatment increased the relative volume of Leydig cells. In addition, ultrastructural evaluation indicated that irrespective of age antiandrogen treatment causes an increase in frequency of organelles involved with steroid hormone synthesis in the Leydig cells and a dramatic accumulation of myelin figures in their cytoplasm and, to a larger degree, in Sertoli cells. In conclusion, the transient exposition of the guinea pigs to flutamide, at all postnatal ages causes some degenerative lesions including severe premature detachment of spermatids and accumulation of myelin bodies in Leydig and Sertoli cells, compromising, at least temporarily, the spermatogenesis.